PERILAKU ELEKTROKIMIA BAJA TAHAN KARAT SS 316 DALAM MEDIA NANO FLUIDA - Prajitno, Djoko Hadi; Setiawan, Jan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Corrosion is a common problem in many engineering metals and alloys. Electrochemical method is powerful instrument to use as tool to study corrosion behavior of metals and alloys in corrosive environment. The present study is to evaluate interaction between stainless steel SS 316 and nanofluid containing nano particles of ZrO2 as an additive to demineralized water by electrochemical method. Corrosion potential, Tafel polarization, and electrochemical impedance spectroscopy (EIS) of stainless steel SS 316 were performed in both demineralized water and demineralized water containing nano particle 0.05% ZrO2 at different immersion time. Corrosion potential examination shows that stainless steel 316 is actively corroded in both demin water and nanofluid. The corrosion potential tends to increase toward positive value for longer immersion time, both in demin water and nanofluid media. The value of anodic Tafel slope of also tends to increase for longer immersion time, both in demin water and nanofluid. Tafel polarization examination shows that corrosion rate of stainless steel 316 in demin water and nanofluid is not significantly different, and corrosion rate decreases with immersion time. EIS technique shows that the impedance of stainless steel 316 in nanofluid is higher when compared to the impedance in demineralized media, resulting in lower corrosion rates in nano fluids. X-ray diffraction examination of the specimens shows that the phase present in the stainless steel 316 alloys after corrosion testing is γ austenite, both in demin water and nanofluid. Stainless steel SS 316 is very good corrosion resistant material both in demin water and nanofluid with corrosion rate under 1 MPY.